Tensoranalysis - Schade, Heinz (Walter de Gruyter, 2006)
Representing an introduction to tensor analysis, this book introduces tensors in symbolic notation and in Cartesian and curvilinear co-ordinates, amongst other things, as well as the algebra of second stage tensors. It imparts the required algebraic aids; and is directed at students on various engineering study courses.